On the Analysis of Three-Dimensional Contingency Tables-Application to the Influence of Allergy and Age on Cancer - Moussa, M. A. A.; Karnik, A. M.; Omar, Y. T.; Fenech, F. F. (Methods of Information in Medicine, 1985)
A procedure is described for the analysis of I × J × K cross-classifications. This includes 1. selecting the appropriate model by iterative proportional fitting of the data to relevant configurations of log-linear models; 2. assumptions underlying reduction of three-way tables to two dimensions; 3. the Mantel-Haenszel statistic with reference to its relation to log-linear models.The methods are applied to a data set based on a study recently conducted at the Cancer Control Centre, Kuwait to investigate the relation between allergy and cancer. It was concluded that the allergy rate is significantly lower in the cancer group which suggests that allergy could be a protective factor against cancer.
Keywords: Three-Way Contingency Tables; Log-Linear Models; Mantel-Haenszel Statistic